UPAYA MENINGKATKAN RASA INGIN TAHU DAN PRESTASI BELAJAR MATEMATIKA MATERI BANGUN RUANG MELALUI MODEL PEMBELAJARAN QUANTUM - Sulistyo, Mahendra (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This research was underlined by students low curiosity and learning achievement on mathematics in grade IV at SD Negeri 1 Kaliwungu. This research was aimed at improving the students’ curiosity and mathematics learning achievement on simple solids through Quantum learning model. The subject of this research was the IV grade students of SD Negeri 1 Kaliwungu consisting of 19 students comprising 8 males and 11 females. This was a classroom action research carried 2 cycles. The procedure in each cycle involved planning, acting, observing, and reflecting. The data were obtained from the observation sheet for the teacher and students activity. To get the data dealing with the learning achievement, the evaluation test was given at the end of each meeting. Moreover, the questionnaire was distributed to the student to get data of students curiosity. Based on the result of the research, the students’ curiosity in the first cycle was 73.81% and in the second cycle was 80.26%. Furthermore, the mastery of students learning achievement in the first cycle was 86.84% and in the second cycle was 89.47%. In conclusion, the Quantum learning model could improve the students’ curiosity and mathematics learning achievement on simple solids in grade IV at SD Negeri 1 Kaliwungu, Mandiraja sub-district, Banjarnegara regency.